Let them cook: Overcoming regulatory hurdles to the growth of local food micro-ventures. Issue 3 (27th May 2018) - Faison, M. James; Leverette, Todd
Abstract: From local community centers, to the halls of Congress, the future of America's food policy is taking center stage. Increases in diet-related health issues, growing populist attitudes about hyperlocal economies, and large private sector investments into new and novel food-related businesses have made the issue of "how Americans eat" almost as important as "what Americans eat." Many of the most important decisions about the future of America's food systems are not being made at the federal or state level, but by local city councils and boards of supervisors. This article offers concrete policy recommendations that local leaders can utilize to grow local food economies that create jobs and more vibrant local communities.